A Novel Deployable Reflector using a Lazy Tong Truss - Nabil Noor Swadi (Engineering and Technology Journal, 2012)
In this paper, a new concept for a deployable parabolic reflector used in SAR satellite has a support based on a two-dimensional lazy tong mechanism is proposed. Two sets of lazy tong mechanisms are used, one at each side, to support the structure through its operation (deploying and folding). The deployment of the structure is controlled by the vertical inward movement of the ends of the first two bars in each mechanism. This movement is directed by the strain energy stored in the helical springs that work at those places. A preliminary design of the quarter scale model of the suggested reflector in deployed configuration is modeled and analyzed using ANSYS software program. The value of the maximum deflection and Von Mises stress due to effect of inertia load only are obtained for the composite material (T300/Hexcel 8552) of the reflective surface and hard aluminum alloys (2024-T3) of the truss. They were 0.465 mm and 23.3 MPa respectively. The linear buckling behavior of the structure is as well studied. The first eigenvalue factor was about 19.639. The theoretical total deploying time and velocity is considered and their magnitudes are about 0.14 sec. and 0.46 m/s respectively. The packaging volume was about 1/6th of deploying volume. The total estimated mass of this quarter scale reflector was approximately 2.5 kg.